Dark sacred night eaudiobook - Connelly, Michael (Renée Ballard, 2018)
Harry Bosch teams up with LAPD detective Renée Ballard to solve the murder of a young girl in the new thriller from #1 New York Times bestselling author Michael Connelly. Detective Renée Ballard is working the night beat — known in LAPD slang as "the late show" — and returns to Hollywood Station in the early hours to find a stranger rifling through old file cabinets. The intruder is retired detective Harry Bosch, working a cold case that has gotten under his skin. Ballard can't let him go through department records, but when he leaves, she looks into the case herself and feels a deep tug of empathy and anger. She has never been the kind of cop who leaves the job behind at the end of her shift — and she wants in. The murder, unsolved, was of fifteen-year-old Daisy Clayton, a runaway on the streets of Hollywood who was brutally killed, her body left in a dumpster like so much trash. Now Ballard joins forces with Bosch to find out what happened to Daisy, and to finally bring her killer to justice. Along the way, the two detectives forge a fragile trust, but this new partnership is put to the test when the case takes an unexpected and dangerous turn. Dark Sacred Night for the first time brings together these two powerhouse detectives in a riveting story that unfolds with furious momentum. And it shows once more why "there's no doubt Connelly is a master of crime fiction" (Associated Press).